Batch kraft cooking of spruce wood - Rahman, Md. Mostafizur; Potůček, František (Slovenská spoločnosť chemického inžinierstva, 2017)
The paper deals with batch kraft cooking of pulp from spruce wood. The kappa number of the cooked pulp varied from 18.1 to 50.1, depending on varying H-factor from 550 to 3 190 h. A relationship between the kappa number of pulp and the H-factor was developed. The conditions were regarded in which rejects were lower than 1 %. It was found that the mass loss of the pulp after the kappa number determination according to TAPPI Test Method was not only responsible for the solubility of residual lignin present in pulp, but also a part of hemicelluloses and cellulose was solubilized.
Diskontinuální sulfátová várka smrkového dřeva
Keywords: batch cook; spruce; kraft pulp; delignification; diskontinuální várka; smrk; sulfátová buničina; delignifikace